Factors Associated with Nurses’ Self-Efficacy in Applying Palliative Care in Intensive Care Unit - Theresia Avila Kurnia; Yanny Trisyani; Ayu Prawesti (Universitas Airlangga, 2018)
Introduction: The increasing need for palliative care (PC) in the intensive care unit (ICU) is characterised by an increasing number of patients with critical and terminals conditions. It requires comprehensive treatment of nurses, through PC. Self-efficacy is a major predictor that affects the application of PC in ICU. Therefore, nurses need to have high self-efficacy to provide quality PC for patients and their families. This study aimed to analyse the factors that dominant relates to nurses' self-efficacy in implementing of providing PC in ICU.Methods: This research was correlational research with cross-sectional survey design. The sampling technique used was total sampling, which involved 127 critical nurses who were actively working at a general hospital in Bandung, Indonesia. Data were collected using questionnaires. Bivariate analysis using Pearson correlation and Rank-Spearman test and multivariate analysis using linear regression.Results: The results showed that the majority of respondents had high self-efficacy, working experience >15 years, enough interest to the nursing profession had less knowledge and negative perception related to the PC in ICU. There was a significant relationship between self-efficacy with work experience, nurses' interest in the nursing profession, knowledge and perception variables. The most dominant factors related to self-efficacy, namely knowledge and perceptions of nurses related to PC.Conclusion: This study indicates that majority of the respondents lacked knowledge and had negative perceptions related to PC in ICU, it is necessary to socialise and training related to it by focusing on self-belief or self-efficacy of nurses on their ability.